Turgenev’s appropriation of King Lear: A case of medieval transmission and adaptation - Bellmunt Serrano, Manel (Moderna Språk, 2019)
This paper tries to provide a thorough analysis of Ivan Turgenev’s appropriation of King Lear, the Shakespearean tragedy, as it appears in the novella King Lear of the Steppes (1870), from the perspective of translation and adaptation studies, and how this was adapted to 19th-century Russia. This analysis highlights the role of cross-cultural relations and its influence on the evolution of target literatures. The comparison with Shakespeare’s source text shows evident similarities but also differences, all of which raise multiple questions from the perspective of philosophy, history and ideology, among others. In fact, the interpretation of Shakespeare’s work, in Turgenev’s work and in the Russian literature as a whole, has become essential to understand the intellectual development of this country since the 19th century, as well as the rise of some debates about the Russian cultural identity, which still continue today. By focusing on Turgenev’s novella King Lear of the Steppes, the relevance of processes such as appropriation and adaptation for the development of national literatures will be underscored and how these foster debate and discussion within cultural systems. And, in order to illustrate this, it will also be highlighted that Shakespeare’s King Lear was in fact based upon several previous medieval sources and suffered multiple changes and adaptations over the centuries, which proves that knowledge transforms and adapts to the literary, cultural and ideological features of each period of time and society.